Compressive sensing MTI processing in distributed MIMO radars. Issue 3 (1st May 2018) - Tohidi, Ehsan; Radmard, Mojtaba; Nazari Majd, Mohammad; Behroozi, Hamid; Nayebi, Mohammad Mahdi
Abstract : It is shown that the detection performance can be significantly improved using the recent technology of multiple‐input multiple‐output (MIMO) radar systems. This is a result of the spatial diversity in such systems due to the viewing of the target from different angles. On the other hand, the moving target indication (MTI) processing has long been known and applied in the traditional pulse radars to detect weak moving targets in the presence of strong clutter signals. The authors propose a procedure based on the compressive sensing idea, in order to apply the MTI processing in a MIMO radar with widely separated antennas. Although a clutter is included in the signal model and a different radar cross‐section value for each transmitter–receiver pair is considered which makes the problem more complex, the complexity dimension is preserved as low as possible by converting the block sparse problem into a regular sparse problem.